STUDI TENTANG HOMOSEKS DAN LESBIAN PERSPEKTIF HUKUM ISLAM - Musfira (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2022)
Homosexuality is a biological relationship between the same sex, both male and female, but the term homosexual is more suitable for sex between men and women. Sexual deviation is not carried out by people who deny existence but Allah and the resurrection today, which is believed to be the existence of Allah and the hereafter. This is because today's human civilization is far from materialism, leaving religion and spiritual values behind. The spread of various means of generating the fire of lust in both urban and rural communities. To avoid the negative consequences of homosexuality, it requires moral development that is in accordance with religious norms and values. And the formation of correct morals is a utopia as long as the materialistic system that is contrary to the principles and religious systems can be enforced in a sustainable manner.